Strategies to Teach English as a Foreign Language in Merdeka Curriculum: A Systematic Literature Review - Rufi’ah Ning Asrianti; Abas Rosadi (Proceedings Series on Social Sciences & Humanities, 2024)
This study uses a qualitative methodology and literature review strategy to explore various approaches to enhance students' English acquisition as a foreign language. Two distinct teaching approaches are identified: Teaching-Centered Learning and Student-Centered Learning. Effective teaching methods include teacher training, participation in English teacher meetings, creating a stimulating learning atmosphere, implementing differentiated learning, and conducting assessments. To address challenges, educators may adopt a novel approach to teaching English, such as the Merdeka curriculum, which incorporates the unique traits of each student based on their Pancasila profile. This curriculum is closely intertwined with ICT advancements from the Industrial Revolution, enhancing students' motivation and engagement in teaching and learning. Instructors must exhibit a proactive and inventive approach to create a captivating educational experience, fostering student engagement and enjoyment. Digital resources like YouTube, SMART-board, Twitter, and blogs can be utilized in the educational process to improve student involvement and efficiency while adhering to the updated curriculum standards.